Peningkatan Keterampilan Menulis Teks Persuasif Melalui Model Pembelajaran Problem-Based Learning Pada Siswa Kelas VIII SMP Negeri 11 Medan - Meilan Rahmah Denny Lubis; Yusni Khairul Amri; Rizal Manurung (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
This study identified the challenges faced by students in writing persuasive texts, as well as exploring the potential for implementing PBL to improve writing skills. This research was conducted using the classroom action research method in class VIII SMP Negeri 11 Medan in the 2022/2023 academic year with a total of 32 students. Actions taken by applying the Problem-Based Learning learning model. This research was conducted in two cycles. Based on the results of research on student activity, it was found that the average value of student activity at the first meeting was 65.15%, at the second meeting, the percentage of activity value was 77.07%. The average value of student activity at meeting III was 70.09%, including the active category. Meanwhile, at the fourth meeting, the percentage of activity values ​​was 72.66% and if it was included in the criteria for student activity, this student activity was included in the active category. Overall, if an average of each cycle is obtained, the results of persuasive text writing skills have increased from 71.61% (active enough category) in cycle I to 71.37% (active category) in cycle II, which means an increase of 9. 76 %. Thus it can be seen that the Problem Based Learning learning model can improve the skills of writing persuasive texts and students understand learning material more easily.